Antler possession by west Greenland female caribou in relation to population characteristics - Thing, Henning; Olesen, Carsten Riis; Aastrup, Peter (Rangifer, 1986)
The frequency of antlerless adult female caribou (Rangifer tarandus groenlandicus) was studied in four separate populations in west Greenland. Between the herds antlerlessness varied from 21% to 79%. An inverse relationship between winter range quality and percentage of unantlered cows is demonstrated. Relationship between calf percentage and maternal antler status was studied in one population and antlerless cows showed higher reproductive rate than antlered ones. In another population antlerless cows were almost absent outside the calving area. Calves of antlerless mothers were more susceptible to diseases and had significantly higher summer mortality than other calves, 42% and 27% respectively. The relative importance of factors influencing antler development under various environmental conditons are assessed and a close relationship between antlerlessness, physical condition, lactation, and length of period between calving and midsummer is discussed.